2001
DOI: 10.1159/000050284
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Comparative Genomic Hybridization and Fluorescence in situ Hybridization to the Detection of Chromosomal Abnormalities in B-Cell Chronic Lymphocytic Leukemia

Abstract: Background: B-chronic lymphocytic leukemia (B-CLL), the most common type of leukemia in Western Europe and the United States, is characterized by clonal chromosomal abnormalities detected in almost half of the studied patients. The precise determination of chromosomal changes helps to indicate the prognosis and to understand the pathogenesis of CLL. Methods and Patients: We applied conventional cytogenetics (CC), FISH and comparative genomic hybridization (CGH) to the investigation of clonal abnormalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…In several studies, chromosomal abnormalities have been reported in 53-77% of CLL patients (29)(30)(31). The most frequently genetic alterations were del 13q, trisomy 12, del 11q, del 17p and del 6q.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, chromosomal abnormalities have been reported in 53-77% of CLL patients (29)(30)(31). The most frequently genetic alterations were del 13q, trisomy 12, del 11q, del 17p and del 6q.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently genetic alterations were del 13q, trisomy 12, del 11q, del 17p and del 6q. It is known that, del 11q and del 17p are associated with high disease activity (30). el Rouby et al (32) investigated p53 mutation in CLL patients and found that p53 mutation was associated with progressed disease.…”
Section: Discussionmentioning
confidence: 99%
“…Complex karyotypes were defined as findings of three and more clonal aberrations in a karyotype. CGH was carried out according to the manufacturer's instructions as described earlier [20].…”
Section: Methodsmentioning
confidence: 99%
“…Using conventional cytogenetic techniques, Jarosova et al (143) found that 17% of nonstimulated bone marrow samples of 88 CLL patients had abnormalities. Comparative genomic hybridization and FISH revealed chromosomal changes in an additional 33 individuals, bringing the total with abnormalities to 57%.…”
Section: Cytogeneticsmentioning
confidence: 99%